2017
DOI: 10.1371/journal.pone.0168842
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Good Governance of Healthcare Technology Management in the Public Sector: Learning from Evidence-Informed Policy Development and Implementation in Benin

Abstract: Good governance (GG) is an important concept that has evolved as a set of normative principles for low- and middle-income countries (LMICs) to strengthen the functional capacity of their public bodies, and as a conditional prerequisite to receive donor funding. Although much is written on good governance, very little is known on how to implement it. This paper documents the process of developing a strategy to implement a GG model for Health Technology Management (HTM) in the public health sector, based on less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…As some authors have pointed out and according to the United Nations national development plan document, the goal of good governance is to achieve sustainable human development that focuses on reducing poverty, creating jobs and sustainable prosperity, protecting the environmental and restoring the environment, and women's growth and development. In fact, it is assumed that all these things will be achieved through good governance (4).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…As some authors have pointed out and according to the United Nations national development plan document, the goal of good governance is to achieve sustainable human development that focuses on reducing poverty, creating jobs and sustainable prosperity, protecting the environmental and restoring the environment, and women's growth and development. In fact, it is assumed that all these things will be achieved through good governance (4).…”
Section: Contextmentioning
confidence: 99%
“…Of course, realizing this issue requires high-level monitoring and supervision, which requires proportional institutional capacity. Political wish is considered from the perspective that the subject of decentralization is considered as one of the main foundations of good governance in health (4). Brinkerhoff (2014) has evaluated the role of good governance in strengthening health systems and pointed to three gaps in health and governance problems.…”
Section: Contextmentioning
confidence: 99%
“…There is evidence to suggest that stakeholder engagement is the key in both implementation and translational sciences which includes tailoring best evidence for policy and practices for specific populations [60]. In Benin, Houngbo et al [61], assessed governance of healthcare technology management and noted that interactive and analytical tools of action research can be used to integrate knowledge amongst actor groups, and that the policy development process was characterized as bottom-up, with a central focus on the participation of diverse stakeholders groups. In another study from Benin, Lee et al [62] while assessing vaccine policy, observed that the enabling change required identifying in-country "champions," and orchestration of a coordinated set of steps that heavily involve key stakeholders.…”
Section: Perform Stakeholders' Analysis and Convene Stakeholders' Engagmentioning
confidence: 99%
“…There is evidence to suggest that stakeholder engagement is the key in both implementation and translational sciences which includes tailoring best evidence for policy and practices for speci c populations [61]. In Benin, Houngbo et al [62], assessed governance of healthcare technology management and noted that interactive and analytical tools of action research can be used to integrate knowledge amongst actor groups, and that the policy development process was characterized as bottom-up, with a central focus on the participation of diverse stakeholders groups. In another study from Benin, Lee et al [63] while assessing vaccine policy, observed that the enabling change required identifying in-country "champions," and orchestration of a coordinated set of steps that heavily involve key stakeholders.…”
Section: Perform Stakeholders' Analysis and Convene Stakeholders' Engagmentioning
confidence: 99%